2023
DOI: 10.3389/fimmu.2023.1104881
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of Smad7 in CD4+ T cells is associated with the disease activity of rheumatoid arthritis

Abstract: BackgroundSmad7 is protective in a mouse model of rheumatoid arthritis. Here we investigated whether Smad7-expressing CD4+ T cells and the methylation of Smad7 gene in CD4+ T cells contribute to the disease activity of RA in patients.MethodsPeripheral CD4+ T cells were collected from 35 healthy controls and 57 RA patients. Smad7 expression by CD4+ T cells were determined and correlated with the clinical parameters of RA including RA score and serum levels of IL-6, CRP, ESR, DAS28-CRP, DAS28-ESR, Swollen joints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…RA, a prevalent immune system disease primarily affecting small and medium-sized joints, has its pathogenesis significantly influenced by the scarcity of Treg cells, a critical immunoregulatory cell type [5,6]. While Treg cell transplantation has shown efficacy in treating RA [40], this approach may encounter challenges such as low specificity and potential for non-specific rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA, a prevalent immune system disease primarily affecting small and medium-sized joints, has its pathogenesis significantly influenced by the scarcity of Treg cells, a critical immunoregulatory cell type [5,6]. While Treg cell transplantation has shown efficacy in treating RA [40], this approach may encounter challenges such as low specificity and potential for non-specific rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T cells (Treg), a specialized subset of CD4 + CD25 + FOXP3 + T cells, play a pivotal role in suppressing autoimmune effector cells, thereby preventing autoimmune diseases and maintaining immune homeostasis [3,4]. A reduction in the proportion of Treg cells and their dysfunction are critical factors in the development and progression of rheumatoid arthritis [5,6]. Collagen-induced arthritis (CIA) mice, a widely recognized mouse model for rheumatoid arthritis, served as the experimental subjects in this study [7].…”
Section: Introductionmentioning
confidence: 99%
“…Th17 cells play an important role in the onset and progression of RA. [ 77 ] Specific gene DNA methylation and histone modifications have been found to play a key role in the development and functional regulation of Th17 cells. For example, the DNA methylation level and histone acetylation level of the IL-17A gene are associated with disease activity in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Smad7 is significantly decreased in CD4 + T cells from rheumatoid arthritis patients, and its content is inversely correlated with rheumatoid arthritis activity scores, serum levels of inflammatory markers (i.e., IL‐6 and C‐reactive protein), and is associated with a high number of Th17 cells. Mechanistically, reduced expression of Smad7 in CD4 + T cells has been associated with DNA methyltransferase‐driven DNA hypermethylation in the Smad7 promoter [110]. Consistently, studies in mouse models of rheumatoid arthritis showed that loss of Smad7 resulted in activation of TGF‐β/Smad3 and NF‐κB pathways and predominant differentiation of Th17 cells, leading to synovial inflammation [108], whereas intraarticular overexpression of Smad7 improved experimental arthritis [111].…”
Section: Inhibition Of Tgf‐β1 Signaling By Smad7 and The Role Of Smad...mentioning
confidence: 97%